Utilization of Tofu Industrial Liquid Waste as Organic Fertilizer to Support the Alley Garden Project Development - Kusumaningtyas, Ratna Dewi; Marwoto, Putut; Wulandari, Cahya; Atuzzuhro, Qoni' (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2020)
Tofu is a food that people are fond of and is recognized as healthy, nutritious and cheap cuisine. The tofu industry has been growing rapidly in Indonesia in the form of household scale businesses or MSME (Micro, Small and Medium Enterprises). On the other hand, tofu industry also has a negative impact to the environment due to its waste. The waste of tofu industry has high level of BOD and COD so that it becomes organic pollutant for groundwater and creates an unpleasant odor. Tofu components that potentially become liquid waste are the organic compounds such as protein (40-60)%, carbohydrates (25-50)%, and 10% fat. The largest component of tofu liquid waste is protein, which is 226.06 mg/L to 434.78 mg/L. This nutrient content allows tofu liquid waste to be processed into liquid organic fertilizer through a simple fermentation process. In this community service project, short training on processing tofu industrial liquid waste into liquid organic fertilizer has been conducted in Sumurrejo are, Semarang. To utilize this organic fertilizer for plant growing, an alley garden was also established in the village.